The effect of dimensions of organizational commitment on nurses\' job attachment in clinical education environments - Seyed Masoud Mousavi; Sajjad Bahariniya; Aisa Mardani; Najmeh Baghian (Tehran University of Medical Sciences, 2024)
Background and Purpose: Organizational commitment among nurses, a critical aspect of hospital workforce management, is influenced by various factors, including job attachment. This attachment fosters motivation and commitment, which ultimately enhances the quality of healthcare services. This study investigates the relationship between organizational commitment and job attachment among nurses working in selected teaching hospitals affiliated with Shahid Sadoughi University of Medical Sciences in Yazd in 2022. Methods: This descriptive-analytical study involved all nurses at Shahid Sadoughi Hospital in Yazd. A sample size of 298 nurses was determined using Cochran's formula. Data collection was conducted using the Job Descriptive Index (JDI) by Edwards and Kilpatrick (1984) and the Organizational Commitment Questionnaire (OCQ) by Allen and Meyer (1990). The data were analyzed using the Chi-square test with SPSS version 21 software and structural equation modeling via LISREL software. Results: Among the nurses surveyed, 43.17% reported being satisfied with their jobs, while 40.17% exhibited organizational commitment. The findings revealed a significant relationship between job attachment and organizational commitment (P<0.001). The average scores were 3.75 ± 0.76 for the affective dimension, 3.97 ± 0.26 for the continuance dimension, 3.65 ± 0.36 for the normative dimension, and 3.74 ± 0.93 for overall job attachment. Conclusion: The significant direct relationship between job satisfaction and organizational commitment highlights the importance of managerial focus on enhancing job satisfaction to increase employee responsibility and commitment. Managers should prioritize factors that improve job satisfaction as a means to strengthen organizational commitment.